Opposite Trends in Holocene Speleothem Proxy Records From Two Neighboring Caves in Germany: A Multi-Proxy Evaluation - Weber, Michael; Hinz, Yvonne; Schöne, Bernd R.; Jochum, Klaus Peter; Hoffmann, Dirk; Spötl, Christoph; Riechelmann, Dana F. C.; Scholz, Denis (Frontiers in Earth Science, 2021)
Holocene climate in Central Europe was characterised by variations on millennial to decadal time scales. Speleothems provide the opportunity to study such palaeoclimate variability using high temporal resolution proxy records, and offer precise age models by U-series dating. However, the significance of proxy records from an individual speleothem is still a matter of debate, and limited sample availability often hampers the possibility to reproduce proxy records or to resolve spatial climate patterns. Here we present a palaeoclimate record based on four stalagmites from the Hüttenbläserschachthöhle (HBSH), western Germany. Two specimens cover almost the entire Holocene, with a short hiatus in between. A third stalagmite grew between 6.1 ± 0.6 ka and 0.6 ± 0.1 ka and a fourth one covers 11.0 ± 0.4 ka to 8.2 ± 0.2 ka. Trace element and stable isotope data allow to compare coeval stalagmites and to reconstruct potential climate patterns in the Holocene. In addition, Sr isotopes reveal soil processes and recharge of the aquifer. The aim of this study was to evaluate the consistency of the proxy data recorded by the individual stalagmites and to validate the results using a multi-proxy approach. Due to the close proximity of HBSH (<1 km) to the intensively investigated Bunker Cave system, this dataset also provides the unique opportunity to compare this record with a time-series from another cave system in the same climate region. While the initial growth phase at the onset of the Holocene shows similar patterns in both caves, the data show an opposing trend in the past 6 ka, most likely induced by the effect of disequilibrium isotope fractionation, resulting in a strong increase in δ13C and δ18O values. The stable isotope data from Bunker Cave do not show this pattern. Trace element data support the interpretation of the HBSH stable isotope data, highlighting the importance of a multi-proxy approach, and the need to replicate speleothem records both within a cave system and ideally using other caves in the region.